Allelopathic hormesis and slow release of lantana (Lantana camara L.) callus extract - Veraplakorn, Varaporn (Agriculture and Natural Resources, 2018)
Lantana camara L. is believed to contain efficient allelochemicals which can affect many plant species. Using allelopathic chemicals to reduce agrochemical doses could benefit humans and the environment. This research aimed to induce lantana callus, to determine its hormesis and to provide a slow-release formulation of callus extract using calcium alginate beads. The results showed that callus was induced and proliferated on Murashige and Skoog (MS) medium containing 21.5 µM 1-naphthalene acetic acid (NAA) in combination with 22.5 µM N6-benzyladenine (BA) and MS medium containing 0.5-2.5 µM 2,4-dichlorophenoxyacetic acid (2,4-D). MS medium containing NAA and BA produced light green and white compact callus (callus NB) while MS medium containing 2,4-D produced light brown compact callus (callus D). Callus D had an inferior effect on seed germination and seedling growth of Brassica campestris var. chinensis to that of callus NB which totally inhibited seed germination at 0.8% extract. The total fresh weight of seedlings increased when treated with aqueous extract of callus D. An extract concentration of 0.8% or 1.0% induced high total fresh weights of 314.7% and 264.6% of the control, respectively. A slow-release formulation of callus D extract in alginate beads was proven by reduction of the allelopathic effect. Beads with 0.0-5.0% extract had no effect on the germination rate and beads with 1.0-4.0% extract did not reduce the total fresh weight of seedlings. This research suggested hormesis of lantana callus and a slow-release formulation using encapsulation as a novel technique for the further development of natural herbicides.